Bob the builder : to the rescue! - Cockle, Jackie; Ball, Sarah; Harbour, Kate.; Morrissey, Neil.; Joyce, Paul K.; HOT Animation (Firm); Hit Entertainment; Lyrick Studios (Allen, TX : Hit Entertainment : Distributed by Lyrick Studios, 2003)
Follows the adventures of an ever-friendly, helper-builder, Bob, and his crew of fun loving machines. Bob, Wendy, Scoop, Muck, Lofty, and others work together, solve problems, and build friendships.
Clocktower Bob -- Scoop saves the day -- Muck gets stuck - - Lofty to the rescue -- Muck's mood -- Sleepless Lofty -- Muck's short cut -- Lofty the soccer star.
Title from container.
Videocassette compilation of episodes of the British animated television production, dubbed into American English.
Includes 4 full-length episodes and 4 mini-adventures.
Music and lyrics, Paul K. Joyce.
Voices: Kate Harbour, Neil Morrissey.
MPAA rating: Not rated.
Keywords: Bob the Builder (Fictitious character) -- Juvenile drama; Construction equipment -- Juvenile drama; Friendship -- Juvenile drama; Cooperation -- Juvenile drama; Feature films; Films for the hearing impaired; Animated films; Children's films; Animated television programs